Shifted Generalized Pascal Matrices in the Context of Cli ord Algebra-Valued Polynomial Sequences - Cação, Isabel (2017)
The paper shows the role of shifted generalized Pascal matrices in a matrix representation of hypercomplex orthogonal Appell systems. It extends results obtained in previous works in the context of Appell sequences whose rst term is a real constant to sequences whose initial term is a suitable chosen polynomial of n variables.